PENGARUH PEMBELAJARAN KONTEKTUAL TERHADAP HASIL BELAJAR IPA SISWA KELAS III SDN 24 POTIANAK TIMUR - Framita, Wulan; Krisnadi, Hery; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the effect of contextual learning on student learning outcomes of natural science class III in the school of East Pontianak 24 State School. The method is the experiment with the form of Pre-Experimental Design Design and equivalent equivalent control group design. The population of all students from two classes is educated 54 people, the sample of this study is students of class A III who direction 26 people as the class of student participation in students of class II B as a control class which is 28 people. , 81 and the average post-test control 74.45. The results of hypothesis testing using t-test (Polled Variance) were obtained tcount = 3.513 while for dk (26 + 28-2 = 52) with significant ? = 5% obtained table = 1.676, which means count> t table, then Ha is accepted, this proves that there is an influence of contextual learning in the learning of Islamic Knowledge. Based on the results of the measurement results (ES) obtained ES = 0.66 which includes the criteria. With this, you can say that you use contextual learning in your learning. Islamic knowledge gives positive influence on the results of class IIIS students' learning outcomes in East Pontianak 24 State School.        Keywords: Influence, contextual, Natural Sciences Learning Outcomes